THE RELATIONSHIP BETWEEN MATHEMATICAL PROBLEM SOLVING ABILITY AND SELF-EFFICACY - Zamnah, Laila Nailah (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2019)
This research aims to analyze the relationship between student self-efficacy and mathematical problem solving ability. The research was conducted in class XI at one of the Vocational High Schools in Ciamis. The instrument used in this research was a test of mathematical problem solving ability and self-efficacy scale questionnaire. Data analysis using correlation analysis with Spearman Rank correlation. The results showed that there was a relationship between students' self-efficacy with students' mathematical solving ability